Pengaruh Ukuran Perusahaan Dan Struktur Aktiva Terhadap Struktur Modal Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Gaol, Feby Yosepha Lumban; Silaban, Adanan; Siboro, Danri Toni (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to examine the influence of company size and asset structure on capital structure in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The sampling technique uses the saturated sampling method. The total research sample is 84 companies with 3 years of research. This research is a quantitative research. The type of data carried out in this study is secondary data, which is in the form of annual reports of food and beverage companies. The analysis method used is multiple linear regression using SPSS version 26 software. Data testing was carried out using descriptive statistical analysis, classical assumption test, multiple linear regression analysis test, determination coefficient and t-test. The results of the study showed that the variable of company size did not have a significant effect on the capital structure. Meanwhile, asset structure has a significant effect on capital structure.